ANTICANCER EFFECT OF 1,2,3-TRIAZOLE-CONTAINING COMPOUNDS. - Roxatoy Egamberdiyeva Mamajonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Natural compounds and derivatives of natural compounds containing 1,2,3-Triazole are widely used in cancer treatment in combination therapy. Although the 1,2,3-triazole moiety does not occur in nature, the production of "1,2,3-triazole-natural compound" hybrids has become active in medicinal chemistry and has attracted interest as an anticancer candidate.